Value Universitas dan Perilaku Cyber Cheating: Analisis Teori Fraud Diamond - Basot, Falentine Yessyani; Yuanita, Dielanova Wynni; Dewi, Christine Novita (Jurnal Pendidikan Akuntansi (JPAK), 2023)
The purpose of this study is to examine the factors that drive accounting students to commit academic fraud based on the fraud diamond theory (pressure, opportunity, rationalization and ability) and technology abuse by considering university values. This study used purposive sampling as a sampling method using a questionnaire. The sample of this research was 170 Bachelor of Accounting students at Christian Private University, Yogyakarta. The data analysis method was processed using the Structural Equation Model (SEM). Specifically, the SEM method chosen is Partial Least Square (PLS) because it can be used to analyze data with a small number of samples (Hair et al, 2014). The results of this study succeeded in proving that pressure, opportunity, rationalization, ability and misuse of technology have a significant positive effect on academic cheating. This revealed that students who study at universities with Christian values still separate spiritual interests and academic achievements.